2012
DOI: 10.4103/0975-3583.98895
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for metabolic syndrome in Asian Indians: A community study from urban Eastern India

Abstract: Objectives:To determine the prevalence of metabolic syndrome and to identify predictors for the same, specific to an underdeveloped urban locale of Eastern India.Materials and Methods:Study design: Population-based cross-sectional study, with multistage random sampling technique. Setting: Urban city-dwellers in Orissa one of the poorest states of Eastern India bordering a prosperous state of Andhra Pradesh of Southern India. Participants: 1178 adults of age 20–80 years randomly selected from 37 electoral wards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
146
10
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(194 citation statements)
references
References 33 publications
27
146
10
2
Order By: Relevance
“…The prevalence of MetS is found to be 34.58 percent among the urban elderly in the Tirupati town. The intact prevalent is less among elderly Goiania population (58.65%) presented in a study by Vieira et al, nearly equals to the study among urban northern Taiwan (34.3%) carried out by Tsou et al and in urban eastern Indian population (33.5%) enlightened by Prasad et al and more among Brazil population (22.7%) explained in a study with Moreira et al 6,[13][14][15] and in population of Mumbai city here Western India i.e. 19.52 percent assessed by Apurva Sawant at al.…”
Section: Discussionsupporting
confidence: 57%
“…The prevalence of MetS is found to be 34.58 percent among the urban elderly in the Tirupati town. The intact prevalent is less among elderly Goiania population (58.65%) presented in a study by Vieira et al, nearly equals to the study among urban northern Taiwan (34.3%) carried out by Tsou et al and in urban eastern Indian population (33.5%) enlightened by Prasad et al and more among Brazil population (22.7%) explained in a study with Moreira et al 6,[13][14][15] and in population of Mumbai city here Western India i.e. 19.52 percent assessed by Apurva Sawant at al.…”
Section: Discussionsupporting
confidence: 57%
“…These changes are conducive to the development of early-onset type 2 diabetes mellitus and accelerated atherosclerosis. [24] Middle to high socioeconomic status significantly contributed to increased risk of MS. [25] As MS and atherosclerosis are most commonly seen high socioeconomic class, Urustambha might also more prevalent in effluent societies by observing this fact Ayurvedic Acharya's might have called Urustambha as "Aadhya roga. "…”
Section: Why Urustambha Is Called As "Aadhya Vata?"mentioning
confidence: 99%
“…Aadhya roga Sedentary life style/metabolic syndrome/ atherosclerosis most commonly seen in higher socioeconomic class [23][24][25] Aahaara Snigdha, ksheera, dadhi, pishtanna, graamya, anupa, audaka mamsa…”
Section: Synonymmentioning
confidence: 99%
“…Authors concluded that metabolic syndrome is a significant public health problem even in one of the poorest states of India. 9 Hence NASH is particularly important in countries like India where metabolic syndrome is on the rise.…”
mentioning
confidence: 99%